The collaborative economy: An opportunity for building the capacities of Saudi university youth - Ibrahim, Khaled Ahmed Abdel-Al; Ismail , Sayed M.; Namaziandost, Ehsan (Research Journal in Advanced Humanities, 2025)
The collaborative economy presents vast opportunities for the Saudi university students to help address issues such as unemployment along with promotion of skills, entrepreneurship, and social capital development. This study analyzes interaction of over 17 thousand students and feedback information from 23 coordinators to understand the essence of collaborative economy, its platforms and how it influences employment and ideas. The research tackles mixed methods and it examines trends, challenges, and possibilities within the collaborative economy with particular attention paid to technology, environmental and social aspects. Significant findings emphasize the significance of collaborative projects including entrepreneurial growth, digital competence, and collaboration between different fields of science as a transformation of the emerging initiatives. As suggestions of this study, stakeholders should encourage growth of networks between schools, start-up companies and industry to enhance the creation of student friendly opportunities and ecosystems. The paper addresses how collaborative economy can be utilized for purpose of empowering Saudi youth with the necessary skills and competencies for success in an increasingly competitive world.